RESTITUSI SEBAGAI HAK PEMULIHAN KORBAN KEJAHATAN: KELEBIHAN DAN KEKURANGANNYA: Restitution as a Form of Recovery For Crime Victims: Strengths and Weaknesses - Aisyah, Putri Romadhatul; Widjajanti, Ermania (AMICUS CURIAE, 2025)
Restitution is also said to be a form of recovery for crime victims that is recognized in the legal systems of many countries, including Indonesia. The concept of restitution aims to return victims to their original position before the crime occurred through providing compensation and other forms of recovery. This journal discusses the importance of restitution as a victim's right to recovery in a criminal act. The research results show that although restitution is recognized as a victim's right, its implementation is often hampered by various factors, including low understanding among law enforcement officials and limited access to information for victims. Other challenges include the economic constraints faced by perpetrators in paying restitution, as well as the lack of effective mechanisms to enforce restitution payments. This journal also highlights the important role of the Witness and Victim Protection Agency (LPSK) in helping victims apply for and obtain restitution as a form of carrying out their duties and permits, although there is still much that needs to be improved in terms of outreach and operational procedures. This article examines 2 (two) legal issues, namely: first, why every perpetrator of a crime must provide restitution to the victim; second, what are the obstacles in implementing the provision of restitution to victims? This journal uses legal research with a normative approach and supporting data in the form of interviews, which aims to find internet-based solutions so that victims can receive their rights, a sense of justice and recovery.